Kaposi's Sarcoma-Associated Herpesvirus Cytotoxic T Lymphocytes Recognize and Target Darwinian Positively Selected Autologous K1 Epitopes - Stebbing, Justin (American Society for Microbiology, 2003)
Kaposi's sarcoma-associated herpesvirus (KSHV) is the infectious cause of Kaposi's sarcoma (KS) and certain lymphoproliferations particularly in the context of human immunodeficiency virus (HIV) type 1-induced immunosuppression. The introduction of effective therapies to treat HIV has led to a decline in the incidence of KS, suggesting that immune responses may play a role in controlling KSHV infection and pathogenesis. Cytotoxic-T-lymphocyte (CTL) activity against KSHV proteins has been demonstrated; however, the identification of KSHV CTL epitopes remains elusive and problematic. Although the herpesvirus genomic layout is generally conserved, KSHV encodes a unique hypervariable protein, K1, with intense biological selection pressure at specific amino acid sites. To investigate whether this variability is partly driven by cellular immunity, we designed K1 peptides that match only the unique viral sequence for every individual studied here (autologous peptides). We identified functional CTL epitopes within K1's most variable areas, and we show that a given individual responds only to autologous peptides and not to peptides from other individuals. Furthermore, these epitopes are highly conserved sequences within KSHV isolates from a specific strain but are not conserved between different strains. We conclude that CTL recognition contributes to K1, and therefore to KSHV, evolution.